Studi Perencanaan Lampu Penerangan Jalan (PJU) di Jalan Utama Penghubung Kecamatan Udanawu Dan Kecamatan Ponggok Kabupaten Blitar - Megi Megi Andarista Andarista (Journal of Science Nusantara, 2023)
Public street lighting is a vital facility to improve traffic safety, and driving especially at night, and can make road users more careful and feel safe from criminal acts. Data for planning were obtained from field observation methods and calculation methods. For field observation data, the data taken was in the form of: length and width of the road, width of the road shoulders, distance between power poles, distance between power poles and the road and supporting data in the form of AHSP, and results of questionnaires and interviews with the village. For data calculations in the form of: light intensity, illumination, luminance, efficacy, distance between PJUs, number of PJU points, electrical power, electrical energy, the angle of inclination of the ornament handlebars and RAB. With a road width of 4.07 m, a length of 3.7 km, and an average shoulder width of 2.07 m, it will be divided into 3 sessions per village. Based on the calculations, the following results are obtained; for session 1 the 50 Watt LED light, the distance from the PJU pole to the road is 1 m, the pole height is 7 m, the arm length is 2 m, the slope of the handlebar ornament is 8.506 o, the light intensity is 437.9 cd, the illumination is 8.18 lux, the illumination is 0.65 cd /m, the distance between the PJU poles is 40 m, the electric power is 1.7 kW, the RAB is Rp. 368,780,000.00. Session 2 40 Watt LED lights, distance from the PJU pole to the road 0.7 m, pole height 7 m, arm length 1 m, handlebar tilt 14 o, light intensity 350.3 cd, illumination 6.29 lux, luminance 0.50 cd/m, the distance between the PJU poles is 50 m, the electric power is 1.12 kW, the RAB is Rp. 311,490,000.00. Session 3 40 Watt LED lights, distance from the PJU pole to the road 1 m, pole height 7 m, arm length 2 m, handlebar tilt 8.506 o, light intensity 350.3 cd, illumination 6.54 lux, luminance 0.52 cd/ m, the distance between the PJU poles is 50 m, the electric power is 0.56 kW, the RAB is Rp. 158,680,000.00. With the PJU planning study for each per-village session passed by section 48, it is hoped that this can be taken into consideration and can assist the village in submitting PJU construction to the Blitar Regency Transportation Service.